From Lifetime Jobs to Churning? - Sylvain Weber; Giovanni Ferro Luzzi (Swiss Journal of Economics and Statistics, 2014)
Using data over 1991–2008 for Switzerland, we investigate job stability through a series of Cox proportional hazards models. Our baseline results show that employment has become less stable for older male workers, with less noticeable change for other groups. However, when destination states are considered in the model, results indicate that younger workers face more transitions towards unemployment than before, whereas older male workers' greater instability is caused by an increase in transitions to inactivity. It thus appears that the situation of young workers has deteriorated, while the evolution of older men's job stability is at least partly explained by the increasing number of early retirements. For women, our results are largely consistent with their increasing participation rate and attachment to the labor market.
Keywords: J63; J62; C41; 330; job stability; tenure; lifetime jobs; duration models; Switzerland